O PROCAMPO no contexto do PRONACAMPO: Estado, políticas públicas e formação política de educadores (as) do campo no IFMA Campus São Luís - Maracanã - ROLIM, Adriana Coimbra (2024)
This dissertation investigates the political training process of rural educators within the scope of the "Programa de Apoio à Formação Superior em Licenciatura em Educação do Campo" (PROCAMPO), in the context of the "Programa Nacional de Educação do Campo" (PRONACAMPO), specifically at the Federal Institute of Education, Science, and Technology of Maranhão (IFMA), Campus São Luís – Maracanã. The study discusses the interaction between the State and public policies, in a scenario marked by contradictions and class conflicts between hegemonic and counter-hegemonic forces. The research adopts a theoretical methodological perspective that combines historical-dialectical materialism and critical analysis of educational policies, addressing the training of rural educators as a space for dispute between different societal projects. The results highlight the importance of political training that considers the specificities and needs of rural populations in a context where neoliberal policies tend to minimize the rights achieved by social movements. The dissertation contributes to the understanding of the contradictions present in the implementation of public policies aimed at rural education and points to the need for teacher training that transcends technicalities and engages in transformative and emancipatory practices. Keywords: